Influence of Chemical and Physical Change of Pollen Microgels on Swelling/De‐Swelling Behavior. Issue 21 (5th November 2020) - Fan, Teng‐Fei; Hwang, Youngkyu; Ibrahim, Mohammed Shahrudin; Ferracci, Gaia; Cho, Nam‐Joon
Abstract : Front Cover : In article number 2000155 by Nam‐Joon Cho and co‐workers, sunflower pollen grains are transformed into soft materials— pollen microgels—for high processability by the soap‐making method. The physical and chemical properties of the sunflower pollen microgel are investigated for different potassium hydroxide concentrations and incubation times.